USM, UM in top 50 in global rankings by subjects - The Edge, Financial Daily (The Edge Communications, 2015)
KUALA LUMPUR: Two Malaysian universities have made it to the top 50 in this year's QS World University Rankings by subjects, compared with just one last year, global higher education research and rankings outfit QS Quacquarelli Symonds said.